2017
DOI: 10.29312/remexca.v0i16.399
|View full text |Cite
|
Sign up to set email alerts
|

Producción y calidad nutrimental de forrajes en condiciones del Trópico Húmedo de México

Abstract: ResumenCon el objetivo de determinar la calidad nutrimental de los forrajes en un sistema de producción de bovinos doble propósito en el sureste de México, se tomaron muestras de forrajes utilizando jaulas de exclusión y del forraje disponible en la pradera mediante Hand Plucking para determinar: contenido de proteína cruda (PC), fibra detergente neutro (FDN), fibra detergente ácido (FDA) y los minerales cobre (Cu), hierro (Fe), cinc (Zn), calcio (Ca), magnesio (Mg), sodio (Na), potasio (K) y fósforo (P) en ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 13 publications
7
9
0
2
Order By: Relevance
“…Typically, when increasing the biomass and the DM, the CP tends to decrease from the effect of dilution of the plant's nitrogen (Patiño et al, 2018), fact that results from the effect of maturity (Van Soest, 1994). However, the lowest content (p0.05) of CP observed in the cool and rainy seasons, in comparison to the dry season (Table 1), is explained by the higher accumulation of biomass that occurs in these two seasons promoted by higher rainfall, fact that causes greater dilution of the nitrogen (Muñoz-González et al, 2016). In this regard, Muñoz-González et al (2016) evaluated three fodder grasses in three seasons of the year in the southeast of Mexico, and they observed that the CP was higher in the dry season (13.9%), intermediate in the cool season (10.8%) and lower in the rainy season (9.3%), behavior similar to the one obtained in this study.…”
Section: Chemical Compositionmentioning
confidence: 90%
See 1 more Smart Citation
“…Typically, when increasing the biomass and the DM, the CP tends to decrease from the effect of dilution of the plant's nitrogen (Patiño et al, 2018), fact that results from the effect of maturity (Van Soest, 1994). However, the lowest content (p0.05) of CP observed in the cool and rainy seasons, in comparison to the dry season (Table 1), is explained by the higher accumulation of biomass that occurs in these two seasons promoted by higher rainfall, fact that causes greater dilution of the nitrogen (Muñoz-González et al, 2016). In this regard, Muñoz-González et al (2016) evaluated three fodder grasses in three seasons of the year in the southeast of Mexico, and they observed that the CP was higher in the dry season (13.9%), intermediate in the cool season (10.8%) and lower in the rainy season (9.3%), behavior similar to the one obtained in this study.…”
Section: Chemical Compositionmentioning
confidence: 90%
“…However, factors such as the season of the year and the population density of plants affect the yield and nutritional quality of the grasses (Freitas et al, 2012;Pereira et al, 2012). In a study it was observed that the Guinea grass presented better chemical composition in the early rainfall season, followed by the winter season, and the worst chemical composition in the dry and late rainfall season ( Juárez et al, 2009); for their part, Muñoz-González et al (2016) reported that the chemical composition was better in the dry season. Although the density of plants has an effect on the biomass production of Guinea grass (Freitas et al, 2012;Pereira et al, 2012), there is no evidence of its effect on the quality of the fodder (Freitas et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The most common pasture-based production system depends on monoculture of grass species, which is the main or only food provided to the cattle (Quero et al 2015), sometimes combining grass with legumes. These systems can have native or improved pastures, whose nutritional quality will mostly depend on the season and the grass and legume species present (Kubkomawa et al 2015;Mu ñoz-González et al 2016). The use of improved pastures has an added advantage in that, with the introduction of exotic species, the quantity and quality of the fodder available for the animals has also improved.…”
Section: Animal Production Systemsmentioning
confidence: 99%
“…However, the use of fire at the end of the dry season is still common in the tropics and evidence has suggested that this practice increases the quality of native grasslands (Mapiye et al 2008;Flores Ancira et al 2016). It has also been suggested that in the rainy season in the humid tropics, there is a lower nutrient density in the grass, and Mu ñoz- González et al (2016) claimed this can be due to a higher proportion of water and stem material in the forage. However, Silva et al (2009) found that as swards reach 95% light interception, the quality of tropical C4 grasses decreases because the structure of the sward changes with less leaf material in proportion to stem and dead material.…”
Section: Nutritionmentioning
confidence: 99%
“…In fact, this species has been defined as seasonally polyestrous, with more evident manifestations of estrous in the autumn [16], the season with greater forage availability in tropical areas [50]. See Figure 2 [51].…”
Section: Breeding Seasonalitymentioning
confidence: 99%